1957
DOI: 10.1149/1.2428576
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Oxidation of Chromium

Abstract: The oxidation of high purity chromium was studied over the temperature range 700°–1100°C using the vacuum microbalance method. Below 900°C conventional oxidation curves were obtained which can be fitted to the parabolic rate law. Above 900°C and for a film thickness of approximately 4800Aå, the rate of oxidation increased in an unusual manner. This increase in the rate of oxidation disappeared on further oxidation. At temperatures of 1050°C and higher a large increase occurred in the rate of oxidation, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 11 publications
1
34
0
Order By: Relevance
“…The past studies of the oxidation kinetics of pure chromium were mostly conducted in pure oxygen atmosphere under the control of partial pressure, 12,14,17,19,20) and the parabolic rate growth of Cr 2 O 3 was realized in the temperature range of 1023 to 1373 K, while the effect of partial pressure of oxygen on the parabolic rate constant value was relatively small. The growth of the Cr 2 O 3 layer seems to be controlled by diffusion of the Cr cation through the Cr 2 O 3 layer because the voids were observed beneath the outer Cr 2 O 3 layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The past studies of the oxidation kinetics of pure chromium were mostly conducted in pure oxygen atmosphere under the control of partial pressure, 12,14,17,19,20) and the parabolic rate growth of Cr 2 O 3 was realized in the temperature range of 1023 to 1373 K, while the effect of partial pressure of oxygen on the parabolic rate constant value was relatively small. The growth of the Cr 2 O 3 layer seems to be controlled by diffusion of the Cr cation through the Cr 2 O 3 layer because the voids were observed beneath the outer Cr 2 O 3 layer.…”
Section: Discussionmentioning
confidence: 99%
“…Early oxidation studies of chromium had been performed from the 1950s to the beginning of the 1970s, and several studies on high temperature oxidation or nitridation behavior of chromium under a pure oxygen or nitrogen gas atmosphere had been reported. [12][13][14][15][16][17][18][19] Lillerud and Kofstad summarized the past oxidation kinetics studies of pure chromium, and discussed in detail the causes for the large variation in parabolic rate constant values reported in numerous past studies. 20,21) However, very few studies of oxidation and nitridation of chromium-based alloys in atmospheric heating have been carried out, 16,22) and no detailed analyses of scale and subsurface regions have yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation behaviour of chromium and the growth mechanism of the Cr 2 O 3 scale have widely been studied [6,7] in the past up to 1100°C and generally under oxygen controlled partial pressure. The results evidence the strong influence of the oxygen pressure on the oxide scales morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…These observations confirm the results of other authors who have predicted the presence of some of these species by thermodynamic calculations. [19][20][21][22][23] Under these conditions of oxidation no evidence was found of the presence of CrO 2 OH(g) and CrO 2 (OH) 2 (g), which had been reported by other authors as the dominant oxyhydroxide vapor species. [8][9][10] The result of the thermogravimetric study of this sample of Cr in Ar + 80% H 2 O at 650°C is shown in Fig.…”
Section: Methodsmentioning
confidence: 47%